Engaging with Our Communities: Future Trends and Opportunities for Reference Services. Issue 4 (8th November 2017) - Thorpe, Clare
Abstract: Libraries across the world are constantly reinventing themselves as they respond to changing community needs and the benefits and challenges posed by new and emerging technologies. This literature review was undertaken to inform a visioning and planning exercise in the Visitor Experience team at State Library of Queensland to identify opportunities and trends for the provision of engaging and relevant reference services. Four key themes are discussed in this review: changing community expectations and user behaviour, defining and measuring the impact of the modern library and reference services, offering flexibility in spaces and service delivery, and the roles of library staff and future skills sets. This review confirms that libraries, specifically reference and information services, remain in a unique position to support their communities in learning, work, recreation, creativity and innovation. The challenge for library leadership is to measure the impact of the library in their local community context.